Bartolomé María de Las Heras, a bishop between two knives - Zegarra Moretti, Carlos (2021)
It is proposed to study the role of the bishops during the execution of the Bourbon reforms of the second half of the eighteenth century in America. For the Peruvian case, historiography has focused solely on the mitrados considered with the epithet of «enlightened bishops» and that, in some cases, have served to be considered collaborators of the regalist plans of the Bourbon administration. This position overshadows the agenda of these prelates and the positions contrary to the regalist policy. Guided by the performance of Bartolomé María de las Heras in his episcopal government of Cusco, it will be shown how he established a front to combat the royal measures that increasingly threatened with greater force the privileges that the Church had enjoyed since its implantation on American soil.